Discovery of novel ATAD2 bromodomain inhibitors that trigger apoptosis and autophagy in breast cells by structure-based virtual screening - Dahong Yao; Jin Zhang; Jinhui Wang; Dabo Pan; Zhendan He (Taylor & Francis Group, 2020)
ATAD2 has been reported to play an important role in the processes of numerous cancers and validated to be a potential therapeutic target. This work is to discover potent ATAD2 inhibitors and elucidate the underlying mechanisms in breast cancer. A novel ATAD2 bromodomain inhibitor (AM879) was discovered by combining structure-based virtual screening with biochemical analyses. AM879 presents potent inhibitory activity towards ATAD2 bromodomain (IC50 = 3565 nM), presenting no inhibitory activity against BRD2-4. Moreover, AM879 inhibited MDA-MB-231 cells proliferation with IC50 value of 2.43 µM, suppressed the expression of c-Myc, and induced significant apoptosis. Additionally, AM978 could induce autophagy via PI3K-AKT-mTOR signalling in MDA-MB-231 cells. This study demonstrates the development of potent ATAD2 inhibitors with novel scaffolds for breast cancer therapy.